Order-disorder transitions of cytoplasmic N-termini in the mechanisms of P-type ATPases. (22nd September 2021) - Hossain, Khondker R.; Clayton, Daniel; Goodchild, Sophia C.; Rodger, Alison; Payne, Richard J.; Cornelius, Flemming; Clarke, Ronald J.
Abstract : Circular dichroism of an H +, K + -ATPase N-terminal peptide at varying trifluoroethanol concentrations is investigated, indicating that its secondary structure is environmentally sensitive. Abstract : Membrane protein structure and function are modulated via interactions with their lipid environment. This is particularly true for integral membrane pumps, the P-type ATPases. These ATPases play vital roles in cell physiology, where they are associated with the transport of cations and lipids, thereby generating and maintaining crucial (electro-)chemical potential gradients across the membrane. Several pumps (Na +, K + -ATPase, H +, K + -ATPase and the plasma membrane Ca 2+ -ATPase) which are located in the asymmetric animal plasma membrane have been found to possess polybasic (lysine-rich) domains on their cytoplasmic surfaces, which are thought to act as phosphatidylserine (PS) binding domains. In contrast, the sarcoplasmic reticulum Ca 2+ -ATPase, located within an intracellular organelle membrane, does not possess such a domain. Here we focus on the lysine-rich N-termini of the plasma-membrane-bound Na +, K + - and H +, K + -ATPases. Synthetic peptides corresponding to the N-termini of these proteins were found, via quartz crystal microbalance and circular dichroism measurements, to interact via an electrostatic interaction with PS-containing membranes, thereby undergoing an increase in helical or other secondary structure content. As well as influencing ion pumping activity, it is proposed that this interaction could provide a mechanism for sensing the lipid asymmetry of the plasma membrane, which changes drastically when a cell undergoes apoptosis, i.e. programmed cell death. Thus, polybasic regions of plasma membrane-bound ion pumps could potentially perform the function of a "death sensor", signalling to a cell to reduce pumping activity and save energy.